(untitled) (SCIÉNDO INGENIUM, 2022)
The aim of this research was to determine the influence of the problem-based learning didactic program on the improvement of critical thinking of third grade high school students, in the area of Social Studies, of San Juan High School, Trujillo, 2020. The methodology was based on an experimental research design, in its pre-experimental form, for which a single group consisting of 20 students was considered. To identify the level of critical thinking, before and after applying the program, whose learning sessions were carried out through the Zoom virtual videoconferencing, the data collection instrument called “Questionnaire to measure the level of critical thinking in the area of Social studies” was used. It should be noted that this instrument was validated by expert judgment and obtained an acceptable reliability coefficient with Cronbach’s alpha consistency index. Hypothesis testing was done through the “student’s t” test. It was concluded that the problem-based learning didactic program influences the improvement of critical thinking in Social studies of third grade students from San Juan High School, 2020, significantly.